2021
DOI: 10.14198/jhse.2022.173.16
|View full text |Cite
|
Sign up to set email alerts
|

Exercise participation and subjective well-being of collegiate athletes during COVID-19 Pandemic

Abstract: While the NCAA grapples with how to return to sport during the COVID-19 pandemic, knowledge of the current exercise habits and well-being of collegiate athletes can better inform strength and conditioning professionals how to adjust periodization plans for the coming year. As collegiate athletes attempt to train independently, there is an opportunity to survey the athletes who normally participate in organized strength and conditioning programs. This study aims to understand current independent exercise regime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
3
0
2
Order By: Relevance
“…The current study revealed that an increased level of pandemic fatigue adversely affected farmers' participation in rural tourism development. Our results support earlier research which showed that many individuals who experienced dissatisfaction, boredom, and tiredness increased their intention to leave their work because of the threat posed by the pandemic [61,62]. Moreover, evidence from the pre-pandemic period also showed that persistent exposure to physical and mental fatigue might negatively affect individuals' participation, such as reducing their job engagement, co-creation intention, and investment motivation, and increasing the intent to leave the organization and the profession [63].…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…The current study revealed that an increased level of pandemic fatigue adversely affected farmers' participation in rural tourism development. Our results support earlier research which showed that many individuals who experienced dissatisfaction, boredom, and tiredness increased their intention to leave their work because of the threat posed by the pandemic [61,62]. Moreover, evidence from the pre-pandemic period also showed that persistent exposure to physical and mental fatigue might negatively affect individuals' participation, such as reducing their job engagement, co-creation intention, and investment motivation, and increasing the intent to leave the organization and the profession [63].…”
Section: Theoretical Implicationssupporting
confidence: 91%
“…(18) This self-reported well-being questionnaire is often used as a repeated measure to investigate changes over time in individuals, or as a general indicator of well-being across the group to understand general patterns. (19) Further, it is found sensitive to variations within and between weeks. (20) The Hooper & MacKinnon questionnaire was later updated by MacLean in 2014.…”
Section: Methodsmentioning
confidence: 99%
“…e Hooper and MacKinnon questionnaire quantified and qualified the wellbeing relative to fatigue, sleep quality, general muscle soreness, stress, and mood [18]. is questionnaire is often used as a repeated measure to investigate the changes over time in individuals or as a general indicator of well-being across the group to understand general patterns [19]. Furthermore, it is found sensitive to variations within and between weeks [20].…”
Section: Study Endpointsmentioning
confidence: 99%